Undergraduate Dental Students’ Perspectives on Anxiety Triggers during Clinical Endodontic Treatment: A Qualitative Study - Ahangari, Zohreh; Sorati, Sadegh; Naseri, Mandana; Sadeghipour, Maryam; alimohammadzadeh, Maryam; Ghafoori, Ali (Journal of Dental School, 2024)
Objectives Dental students experiencing stress and anxiety employ various coping strategies. Therefore, understanding these experiences is crucial for designing effective interventions. This qualitative study aimed to explore the coping strategies used by endodontic students at Shahid Beheshti University of Medical Sciences in Tehran, Iran. Methods A qualitative content analysis was conducted on 10 purposively selected students from the Department of Endodontics at the Faculty of Dentistry in 2019. In-depth semi-structured interviews were conducted over three months. The interviews were recorded and transcribed verbatim. Data analysis was performed using the Dickelman’s method. Results After coding the interview transcripts, four major themes related to student anxiety were identified: “endodontic department”, “education”, “clinical practice”, and “students”. According to the findings, the main sources of anxiety among students in dental education were professor-student interactions, challenging preclinical courses, the clinical learning environment, and a perceived lack of support. Conclusion While some students demonstrated resilience, others struggled with ineffective coping strategies, potentially affecting their learning and wellbeing. The study identified various sources of anxiety among dental students, including curriculum factors, interactions with the faculty and staff, clinic facilities and equipment, radiography procedures, and preclinical training. Overall, the findings emphasize the need for a comprehensive approach to improve the educational environment.